TINJAUAN YURIDIS PENGGUNAAN MEREK SECARA TANPA HAK MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Dara Quthni Effida (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
Intellectual Property Rights (IPR) protection is a prerequisite for international sales arrangements, this also affects the regulation of IPR at the national level, Indonesia has ratified many international agreements on IPR and revised IPR laws in accordance with the times. History of Indonesian Trademarks Laws has been amended several times. Changes to the law are carried out to carry out legal order of famous brands and brands. The latest change to the trademark law is the issuance of Law Number 20 Year 2016 concerning Trademarks and Geographical Indications.The use of trademarks without rights is often done by business actors because it is related to the function of the brand as the identity of a product or service that has a reputation and is also related to the function of the brand as a guarantee of the quality of the goods. This is because in the brand inherent economic advantages, especially famous brands. Famous brands are often the object of violation because they are related to the reputation of the famous brand. The concept of Legal Protection of Trademark Rights and the Legal Consequences of the Use of Trademarks Without Rights According to Law Number 20 Year 2016 Regarding Trademarks and Geographical Indications is a problem in this study.Keywords: trademark, legal consequences, use of trademarks without rights.